Natural disaster emergency response from a public policy perspective: a four-party evolutionary game among government, international organizations, healthcare institutions, and enterprises - Wu, Baoling; Zhang, Tao; Wang, Xi; Liang, Jiakai; Liu, Mingke; Zheng, Yifan; Liang, Jiarui; Chen, Zhengyu (Frontiers in Public Health, 2025)
ObjectiveThis study utilizes evolutionary game theory to analyze the collaborative evolutionary mechanisms among governments, international organizations, healthcare institutions, and enterprises in natural disaster emergency response, aiming to explore how public policy can optimize the behavior of each stakeholder.MethodsA four-party evolutionary game model was constructed to examine strategy interactions and cooperative mechanisms among all parties. Numerical simulations were conducted to verify how key parameters affect the evolutionary outcomes.ResultsThe results indicate that government regulatory intensity, intervention strategies of international organizations, the philanthropic orientation of healthcare institutions, and the sense of corporate social responsibility among enterprises significantly influence the efficiency of emergency response. Numerical simulations further show that increasing government penalties, reducing international organizations’ dependency losses, improving the resource utilization efficiency of healthcare institutions, and raising both the cost of non-compliance and the market trust benefits for enterprises can encourage stakeholders to adopt more cooperative strategies that serve the public interest.ConclusionThis study reveals the “double-edged sword effect” of government regulation, the “time window effect” of international organizational intervention, the “multiplier effect” of resource efficiency in healthcare institutions, and the “trust-benefit mechanism” of corporate social responsibility, offering new insights for optimizing public policy.